2018
DOI: 10.1016/j.immuni.2018.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Pan-ebolavirus Antibody Recognizes a Site of Broad Vulnerability on the Ebolavirus Glycoprotein

Abstract: SummaryEbolaviruses cause severe disease in humans, and identification of monoclonal antibodies (mAbs) that are effective against multiple ebolaviruses are important for therapeutics development. Here we describe a distinct class of broadly neutralizing human mAbs with protective capacity against three ebolaviruses infectious for humans: Ebola (EBOV), Sudan (SUDV), and Bundibugyo (BDBV) viruses. We isolated mAbs from human survivors of ebolavirus disease and identified a potent mAb, EBOV-520, which bound to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(100 citation statements)
references
References 52 publications
2
97
0
1
Order By: Relevance
“…If the GP was treated with thermolysin first, all nine GC-specific antibodies showed greatly reduced binding ( Figures 2C and S2). A similar observation was made recently for the GC-specific mAb EBOV-442 (Gilchuk et al, 2018). Although not definitive, these results suggest that some antibodies bound to the glycan cap may neutralize either through interference with cathepsin cleavage or by stabilizing the glycan cap in the bound state despite thermolysin cleavage.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…If the GP was treated with thermolysin first, all nine GC-specific antibodies showed greatly reduced binding ( Figures 2C and S2). A similar observation was made recently for the GC-specific mAb EBOV-442 (Gilchuk et al, 2018). Although not definitive, these results suggest that some antibodies bound to the glycan cap may neutralize either through interference with cathepsin cleavage or by stabilizing the glycan cap in the bound state despite thermolysin cleavage.…”
Section: Discussionsupporting
confidence: 86%
“…These results suggested that the P6, 040, and other neutralizing GC-specific antibodies may have either inhibited cleavage of GP by thermolysin or stabilized the glycan cap in the bound state despite cleavage. A related observation has been made recently with the GC-specific mAb EBOV-442 (Gilchuk et al, 2018).…”
Section: Mucin-like Domain-dependent Antibodiessupporting
confidence: 63%
See 1 more Smart Citation
“…Such antibodies may as well offer cross-protection against related viruses. Antibodies targeting conserved epitopes in the stem regions of glycoproteins of the enveloped virus including influenza virus and ebolavirus offer protection against a wide range of antigenically distinct variants [46][47][48]. Likewise, the generation of antibodies targeting the conserved S2 stem of the coronavirus spike protein that can cross-bind spikes of related coronaviruses may even allow the development of mAbs with broad protection against related future emerging coronaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…These are, to our knowledge, the lowest single doses (0.8-1.3 mg total mAb) and longest post-exposure treatment windows (4-5 days) demonstrated to protect guinea pigs from lethal ebolavirus challenge. All previous studies with both therapeutic mAbs and mAb cocktails used total doses of 5-10 mg and did not report initial mAb treatments past 3 days post-exposure 15,16,[33][34][35][36] .…”
mentioning
confidence: 99%